Pengaruh Model Pembelajaran Problem Based Learning (PBL) Terhadap Hasil Belajar Siswa Kelas Ⅳ SD Inpres 1 Tanamodindi - Novia Dewi Santika Tanggolu; Nuraini Nuraini; Azizah Azizah; Khairunnisa Khairunnisa (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2025)
The Influence of the Problem-Based Learning (PBL) Model on the Learning Outcomes of Fourth-Grade Students at SD Inpres 1 Tanamodindi The problem examined in this study is the low learning outcomes of students in science subjects. This study aims to determine the influence of the Problem-Based Learning (PBL) model on the learning outcomes of fourth-grade students at SD Inpres 1 Tanamodindi. This study employed a quasi-experimental design using a non-equivalent pretest–posttest control group design. The population of this study consisted of Class IV A as the experimental group and Class IV B as the control group. The sample included all students from both classes, with 19 students in the experimental class and 19 students in the control class, resulting in a total of 38 participants. Data were collected through tests and documentation. Data analysis involved prerequisite tests, including normality tests and homogeneity tests, followed by hypothesis testing using the IBM SPSS Statistics 25 program. Based on the results of hypothesis testing using the Paired Samples t-test, a significant value (sig. 2-tailed) of 0.000 was obtained from the pretest and posttest scores of the experimental class. Since 0.000 < 0.05, the null hypothesis (H₀) was rejected and the alternative hypothesis (H₁) was accepted. Therefore, it can be concluded that the Problem-Based Learning (PBL) model has a significant influence on the learning outcomes of fourth-grade students at SD Inpres 1 Tanamodindi.